2020
DOI: 10.4103/jwas.jwas_59_21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glaucoma on the mental health of primary open-angle glaucoma patients attending a teaching hospital in South East Nigeria

Abstract: Objective: To evaluate the effect of glaucoma on the mental health of primary open-angle glaucoma patients using Hospital Anxiety and Depression Scale (HADS) Materials and Methods: This was a hospital-based comparative study in which 180 glaucoma patients and controls 18 years and above who met the inclusion criteria were selected consecutively in the Eye Clinic of Federal Medical Centre, Owerri, Imo State, in 2017. Data were collected using a questionnaire and the HADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
0
1
2
Order By: Relevance
“…It is in harmony with the study of Lim et al (2016) , reporting higher depression and anxiety in females than in male glaucoma patients. While it is at variance with the report by Ubochi et al (2020) which revealed that males had higher depression and anxiety scores than females. As glaucoma and depression are known to be more common among female individuals, the ratio of female patients and the differences in methodology may interfere with the outcome ( El-Mogy et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…It is in harmony with the study of Lim et al (2016) , reporting higher depression and anxiety in females than in male glaucoma patients. While it is at variance with the report by Ubochi et al (2020) which revealed that males had higher depression and anxiety scores than females. As glaucoma and depression are known to be more common among female individuals, the ratio of female patients and the differences in methodology may interfere with the outcome ( El-Mogy et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 79%
“…It is in harmony with the study of Lim et al (2016), reporting higher depression and anxiety in females than in male glaucoma patients. While it is at variance with the report by Ubochi et al (2020) which revealed that males had higher depression Genetic causal associations between psychiatric disorders and glaucoma.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The impact extends to various aspects of life, including social interaction, independence, and daily functioning. The condition exacerbates feelings of uncertainty, vulnerability, and a diminished sense of independence, as highlighted by the Glaucoma Research Foundation 16 . This can lead to social isolation, with patients withdrawing from activities and interactions they previously enjoyed 17 .…”
Section: Resultsmentioning
confidence: 99%